Design of Thin Surfaced Asphalt Pavements. (2016) - Leischner, Sabine; Wellner, Frohmut; Falla, Gustavo Canon; Oeser, Markus; Wang, Dawei
Abstract: Thin flexible pavements are widely used worldwide in scarcely populated areas. However, this kind of pavement structure is not widely used in Germany. As a result, no M-E design procedure exists. Recently, a research project aiming to understand the response of thin asphalt pavements under design conditions in Germany showed that the durability of pavements with less than 50 mm asphalt thickness proved to be satisfactory; provided that the design is performed considering the non-linear behaviour of the UGM's in the base course. It was concluded that granular materials in the vicinity of the load must be modelled using non-linear stress dependent models. The paper presents an M-E design approach for thin surfaced asphalt pavements.